'But Why is this so Important?': Discussing Historical Significance in the Classroom. Issue 1 (1st December 2013) - van Drie, Jannet; van Boxtel, Carla; Stam, Brenda
Abstract : Engaging students in historical reasoning is considered important to develop students' historical understanding and historical reasoning ability, but it also raises the question of how to enhance and stimulate students' historical reasoning in the classroom. We will argue why and how discussing historical significance can engage students in historical reasoning. We designed a series of lessons on determining historical significance, based on three approaches to trigger and support historical reasoning: (1) open-ended tasks or questions that are meaningful from both a curriculum and a pupil perspective; (2) engaging students in historical reasoning through small group and whole-class discussions; and (3) using external representations as tools for reasoning. In a small-scale study we investigated whether this approach resulted in historical reasoning in talk and writing and what the quality of this historical reasoning was. Two teachers and their students (in sum 43, 15-16 years of age) participated in the study. Data included a pre- and post-test measuring historical knowledge, student-essays and transcripts of whole-class discussions. Outcomes support the idea that engaging students in issues of historical significance does trigger historical reasoning, however they also reveal that students have difficulties with different aspects of it.